Nueva especie Amazónica de Ptichopus Kaup (Coleoptera: Passalidae) - Da Fonseca, Claudio R.V.; Reyes Castillo, Pedro (Instituto de Ecología, A.C., 1994)
Ptichopus hylaius sp nov., frorn the Brazihan States of Mato Grosso and Rondonia, Amazonas basin, is described and (igured. A key to the species of the neotropical genus Ptichopus Kaup is given. New Information is provided for the holotypes of Ptichopus metzeri luederwaidt and Ptichopus borellii Rosmini, júnior synonyms of Ptichopus angulatus (Percheron).